Rail on Linear Stochastics Supports - Moravčík, M. (Engineering Transactions, 1995)
The field tests revealed that the vertical rail deflection under various service conditions is of a random character. The static linear rail response under vertical wheel load P = 1 kN the rail deflection and the bending moments of the rail are presented. The stiffnesses of fasteners, sleepers and subgrade are included by a set of discrete springs. The linear finite element procedure is applied. Parametric studies are carried out to examine the effect of randomly variable stiffnesses of the supports. Two types of reduction of the support stiffness are modelled: the nonstationary reduction in the stiffnesses of some supports, and the stationary random reduction in stiffnesses of the supports. The deterministic response results and the random ones are compared.